Respostas
respondido por:
13
(a+b)² = a²+2ab+b²
(a-b)² = a²-2ab+b²
(a+b)²-(a-b)²
para a=25 é 1000
a²+2ab+b²-(a²-2ab+b²)
4ab
4.(25).b=1000
100.b=1000
b=10
(a-b)² = a²-2ab+b²
(a+b)²-(a-b)²
para a=25 é 1000
a²+2ab+b²-(a²-2ab+b²)
4ab
4.(25).b=1000
100.b=1000
b=10
dudapazin:
obrigada
respondido por:
10
o valor da expressao (a+b)2-(a-b)2 , para a=25, é 1000. qual o valor de b?
(a+b)2-(a-b)2 = 1000.
a²+2ab+b² -(a²-2ab+b²) = 1000.
a²+2ab+b² - a²+2ab-b² = 1000.
4ab = 1000
4.25b = 1000
100b = 1000
b = 10
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás